#TITLE_ALTERNATIVE# - WASIK ATUL ULUM (nim: 12009070), BINTI
The Central Sumatra Basin is one of the major petroleum basins in Indonesia. The previous study states that there are three pore pressure conditionsin this basin: hydrostatic, underpressure, and overpressure. However, the previous study was based only on pore pressure measurement data without considering physical properties of rock and it is only limited to Sihapas Group. Therefore, a comprehensive understanding of pore pressure characteristics is still required to anticipate potential problems related to pore pressure in this area. The data used in this study area are pore pressure measurement, vitrinite reflectance, SEM (Scanning Electron Microscope), and 2D seismic. The data are coming from 11 exploration wells and two production wells owned by PT Chevron Pacific Indonesia, located at North Aman Trough, South Balam Trough,Rokan High, and Kopar Platform. In this study, pore pressure in sandstone is determined by using RFT data, while for the pore pressure in shale, it is determined by using wireline logs. The comprehensive analysis is performed by combining all data as stated previously. In general, the presence of hydrostatic is observed at Petani and Telisa formations. Meanwhile, underpressure condition presents at Sihapas and part of Pematang Groups. The top of overpressure condition is generally found in Brown Shale Formation. The underpressure condition in study area is generated by hydrodynamic flow (differential recharge and discharge). The overpressure generating mechanism in the study area is fluid volume increase (non-loading),caused by hydrocarbon generation and smectite Ã‚Â– illite diagenesis.<palign="justify">